Nanocarriers of Miconazole or Fluconazole: Effects on Three-Species Candida Biofilms and Cytotoxic Effects In Vitro - Morais Caldeirao, Anne Caroline; Araujo, Heitor Ceolin [UNESP]; Arias, Lais Salomao [UNESP]; Carmona, Wilmer Ramirez [UNESP]; Miranda, Gustavo Porangaba; Penha Oliveira, Sandra Helena [UNESP]; Pessan, Juliano Pelim [UNESP]; Monteiro, Douglas Roberto [UNESP] (Mdpi, 2021)
The contribution of different Candida species in oral fungal infections has stimulated the search for more effective therapies. This study assessed the antibiofilm effects of nanocarriers of miconazole (MCZ) or fluconazole (FLZ) on Candida biofilms, and their cytotoxic effects on murine fibroblasts. Three-species biofilms (Candida albicans/Candida glabrata/Candida tropicalis) were formed on 96-well plates, and they were treated with nanocarriers (iron oxide nanoparticles coated with chitosan-IONPs-CS) of MCZ or FLZ at 39/78/156 mu g/mL; antifungals alone at 156 mu g/mL and artificial saliva were tested as positive and negative controls, respectively. Biofilms were analyzed by colony forming units (CFU), biomass, metabolic activity, and structure/viability. The cytotoxicity (L929 cells) of all treatments was determined via 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) reduction assay. Data were submitted to one- or two-way ANOVA, followed by Tukey's or Fisher LSD's tests (p < 0.05). IONPs-CS-MCZ at 78 mu g/mL promoted similar antibiofilm and cytotoxic effects compared with MCZ at 156 mu g/mL. In turn, IONPs-CS-FLZ at 156 mu g/mL was overall the most effective FLZ antibiofilm treatment, surpassing the effects of FLZ alone; this nanocarrier was also less cytotoxic compared with FLZ alone. It can be concluded that both nanocarriers are more effective alternatives to fight Candida biofilms compared with their respective positive controls in vitro, being a promising alternative for the treatment of oral fungal infections.
Keywords: antifungals; biofilms; Candida; chitosan; cytotoxicity; fluconazole; iron oxide nanoparticles; miconazole; murine fibroblasts; nanocarriers